Stochastic mobility models in space and time - Lorenzo Valerio (Mathematical Sciences, 2013)
An interesting fact in nature is that if we observe agents (neurons, particles, animals, humans) behaving,or more precisely moving, inside their environment, we can recognize - tough at different space or time scales - very specific patterns. The existence of those patterns is quite obvious, since not all things in nature behave totally at random, especially if we take into account thinking species like human beings. On the contrary, their analysis is quite challenging. Indeed, during the years we can find in the literature a lot of efforts to understand the behavior of complex systems through mathematical laws.